2020
DOI: 10.1371/journal.pone.0232531
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of atherosclerosis associated with pesticide exposure in rural areas in Korea

Abstract: Atherosclerosis is a progressive inflammation in systemic vessels, and pesticide exposure has been emerging as its risk factor. This cross-sectional study investigated the association between pesticide exposure and the risk of atherosclerosis in a rural population in Korea using carotid intima-media thickness (CIMT). This study used dataset from the baseline survey of the Korea Farmers Cohort Study between November 2005 and January 2008, and the final analysis included 477 participants. Well-structured questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Worldwide, few studies have used algorithms and indexes to estimate the exposure of occupationally exposed populations. Association between the intensity of the exposure and the biomarkers measured was already described (Intayoung et al, 2021;Fuhrimann et al, 2020;Park et al, 2020). However, to our knowledge, none study has focused in differentiate and validate the classification of occupationally exposed subjects into different levels of risk/exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Worldwide, few studies have used algorithms and indexes to estimate the exposure of occupationally exposed populations. Association between the intensity of the exposure and the biomarkers measured was already described (Intayoung et al, 2021;Fuhrimann et al, 2020;Park et al, 2020). However, to our knowledge, none study has focused in differentiate and validate the classification of occupationally exposed subjects into different levels of risk/exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Carotid intima‐media thickness (CIMT) and epicardial fat thickness (EFT) are both ultrasonographic measurement methods used to demonstrate visceral adiposity and therefore atherosclerosis, and it has been reported that they may be independent risk factors for coronary artery disease 30–32 . CIMT has also been accepted as a measure of occult systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…and it has been reported that they may be independent risk factors for coronary artery disease. [30][31][32] CIMT has also been accepted as a measure of occult systemic inflammation. Therefore, both methods have been examined in inflammatory dermatological diseases such as rosacea for the investigation of cardiovascular relation.…”
Section: Discussionmentioning
confidence: 99%
“…Common carotid artery 45 [21,13,14,140,146,112,142,147,148,17,113,149,139,114,115,133,124,145,119,128,125,141,129,116,132,144,126,150,120,151,121,130,143,22,117,134,152,127,153,122,154,123,138,118] Internal carotid artery 1 [137] Brachial carotid artery 2 [155,156] Femoral artery 1 [135] Not reported 1 [131] Aspect of vasculature assessed…”
Section: Vascular Bed Assessedmentioning
confidence: 99%
“…Atherosclerosis and carotid plaques 19 [21,13,14,140,142,147,17,149,139,136,125,141,151,155,22,123,118] Arterial stiffness 3 [113,129,138] Arterial thickness 14 [135,148,137,114,115,133,124,119,144,126,121,130,156,153,122] Nonspecific cardiovascular risk factors 12 [146,112,114,115,145,131,116,150,120,143,134,127] Organ damage 1 [128] Not reported 1 [154] Technique Ultrasound 49…”
Section: Vascular Bed Assessedmentioning
confidence: 99%